2015
DOI: 10.1016/j.ophtha.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Characteristics of Childhood-Onset Stargardt Disease

Abstract: PurposeTo describe the clinical and molecular characteristics of patients with childhood-onset Stargardt disease (STGD).DesignRetrospective case series.ParticipantsForty-two patients who were diagnosed with STGD in childhood at a single institution between January 2001 and January 2012.MethodsA detailed history and a comprehensive ophthalmic examination were undertaken, including color fundus photography, autofluorescence imaging, spectral-domain optical coherence tomography (SD-OCT), and pattern and full-fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
161
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 154 publications
(174 citation statements)
references
References 36 publications
9
161
2
2
Order By: Relevance
“…Whereas, molecular diagnostic testing for ABCA4-associated diseases was requested for a majority (113 of 150) of patients. The rate of detection of causative mutations in these patients varies between 50% to 80%, depending on testing methods and patient ethnicity (Braun et al, 2013;Fujinami et al, 2015). In a previous study, we observed causative mutations in 48% of patients diagnosed with ABCA4-associated disease, whereas mutations were found in 59% of the probands in the current study by screening the coding region of the ABCA4 gene (Downs et al, 2007).…”
Section: Discussionmentioning
confidence: 42%
“…Whereas, molecular diagnostic testing for ABCA4-associated diseases was requested for a majority (113 of 150) of patients. The rate of detection of causative mutations in these patients varies between 50% to 80%, depending on testing methods and patient ethnicity (Braun et al, 2013;Fujinami et al, 2015). In a previous study, we observed causative mutations in 48% of patients diagnosed with ABCA4-associated disease, whereas mutations were found in 59% of the probands in the current study by screening the coding region of the ABCA4 gene (Downs et al, 2007).…”
Section: Discussionmentioning
confidence: 42%
“…Function and structure of the central macula are affected in various diseases in childhood such as Stargardt disease, achromatopsia and x-linked juvenile retinoschisis [33][34][35]. Although not always in agreement, a combination of mfERG and OCT provides important and complementary information about the central retina [36].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] A combination of disease-causing ABCA4 alleles may, therefore, result in a severe, early-onset STGD1 phenotype (i.e., onset 10 years of age), 11,12 which is often observed as rapidly progressive cone-rod dystrophy, 5,13 in classical STGD1, 10 or in late-onset STGD1. [14][15][16] In about half of the patients with late-onset STGD1 (onset >44 years of age), only one disease-causing allele was identified, despite the sequence analysis of all coding variants.…”
mentioning
confidence: 99%